Challenges In Implementing The Independent Curriculum In The Subject Of Islamic Cultural History At MAN 1 Bojonegoro - Burhanuddin, Hamam; Qodriyah, Irvia Nazilatul; Fauziah, Zumrotul (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2024)
Learning Islamic Cultural History has been considered a difficult lesson to understand, so this obstacle has become a problem and dilemma for educators and students at MAN 1 Bojonegoro, including in facing curriculum changes, namely the Merdeka curriculum. The purpose of this study is to describe the implementation, identify challenges, and explain the efforts made by teachers in facing the challenges of implementing the Merdeka curriculum in the Islamic Cultural History subject. The approach used in this research is a descriptive qualitative approach. Data collection was carried out using observation, interview, and documentation techniques. Based on the results of the research that has been carried out, the following results are obtained: (1) the implementation of the Merdeka curriculum in the Islamic Cultural History subject is carried out through three stages including planning, implementation, and evaluation (2) the challenges include, the guidelines for the formulation of learning tools that are published late, the lack of time for teachers to understand and prepare the independent curriculum, the update of information on the platform that is continuing and has not been completed, the lack of reference materials for examples in implementing the independent curriculum, teachers have difficulty integrating with other teachers due to differences in perceptions and understanding of other teachers about the independent curriculum, the implementation of diagnostic assessments takes a long time. (3) the efforts made by teachers in dealing with it, including following and adjusting existing guidelines, participating in MGMP SKI as well as technical guidance on the Merdeka curriculum from the Indonesian Ministry of Religion, and discussing with students what difficulties they face and then finding solutions together. Keywords: Challenges, Independent Curriculum, History of Islamic Culture